A data-model comparison pinpoints Holocene spatiotemporal pattern of East Asian summer monsoon. (1st June 2021) - Zhang, Haiwei; Zhang, Xu; Cai, Yanjun; Sinha, Ashish; Spötl, Christoph; Baker, Jonathan; Kathayat, Gayatri; Liu, Zhengyu; Tian, Ye; Lu, Jiayu; Wang, Zhenqian; Zhao, Jingyao; et al.
Abstract: Conflicting reconstructions of Holocene variability of the East Asian summer monsoon (EASM) from speleothem versus other types of proxy records have yielded widely divergent estimates of its phase relationship with the Indian summer monsoon (ISM) and Northern Hemisphere summer insolation (NHSI). This apparent discrepancy has been partly attributed to the uncertainties in the climatic representation of Chinese speleothem oxygen isotope (δ 18 O) records. Here we present a composite speleothem δ 18 O record of the last ∼14 kyr from Shennong Cave in southeastern China and model-simulated data of rainfall and meteoric δ 18 O over eastern China. Our synthesis of the proxy-model data suggests that the spatial patterns in both speleothem δ 18 O and paleo-rainfall over eastern China during the Holocene are diverse at orbital and multi-millennial scales. Our findings imply that: 1) speleothem δ 18 O in the EASM regime is largely controlled by the large-scale circulation and concomitant latitudinal shifts of the monsoon rain belt; notwithstanding the heterogeneous spatiotemporal pattern of Holocene rainfall as inferred from various proxy records, a coherent orbital-scale speleothem δ 18 O variability across most Asian monsoon regions (except southeastern China) indeed stems from the NHSI-forced changes in overall monsoon intensity; overall monsoon intensity is not equivalent to monsoon rainfall amount but a manifestation of the large-scale atmospheric circulation; 2) divergent phase relationships with NHSI between speleothem δ 18 O and other proxy records are consistent with—rather than contradictory to—the NHSI forcing mechanism. Speleothem δ 18 O and rainfall records reflect two different aspects of the monsoon dynamics. These results may thus, largely help to reconcile the divergent views of the Holocene Asian monsoon variability. Highlights: Holocene speleothem δ 18 O and rainfall show heterogeneous pattern in eastern China. East Asian speleothem δ 18 O reflects large-scale circulation and monsoon rain belt shift. Divergent phases between speleothem and other proxy records are not contradictory.